IMPLEMENTASI PENGGUNAAN SSP(SUBJECT SPECIFIC PEDAGOGY) TEMATIK INTEGRATIF UNTUK MENANAMKAN TANGGUNG JAWAB, KERJA KERAS, DAN KEJUJURAN - Purwanti, Eri (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2016)
Abstract This study aims to describe and interpret the implementation of SSP thematic integrative use to instill responsibility, hard work and honesty in social studies. The subjects were teachers grade II and grade II SD. Data collected by the techniques of documentation, interviews, and observation and analyzed by data reduction, data presentation, and conclusion. The results of this study are as follows. (1) The teacher already understand thematic learning, but still there are two teachers who do not understand it. (2) Teachers are already planning a thematic learning by using SSP in instilling responsibility, hard work and honesty (3) teaching method applied to the teachers in the implementation of thematic learning the method of lecture and cooperative. (4) The use of SSP can instill responsibility, hard work and honesty on students in social studies. Key words: Thematic, SSP, hard work, honesty, responsibility.